Diversidade da Heterocromatina na subtribo Laeliinae (Epidendroideae: Orchidaceae), com ênfase no gênero Cattleya Lindl. - Souza, Bruno César Querino de (2015)
The subtribe Laeliinae comprises about 2000 species in 38 genera, exclusively neotropical and is considered the third largest family of subtribe. Cytological features most species with basic chromosome number x = 20 and karyotype evolution mainly associated with polyploidy. This study aimed performed a comparative cytogenetic analysis in 42 species of Laeliinae subtribe based on banding fluorochromes with CMA/DAPI, and estimate the nuclear DNA content of many of these species through citmetria of flow. All species presented 2n = 40 except Cattleya nobilior with 2n = 42 and the polyploid C. elongata, C. crispata, Encyclia alboxanthina, E. jenischiana, E. seidelii, Laelia gouldiana and Prosthechea faresiana (2n = 80). We observed two blocks CMA+/DAPI terminals in all species. The DNA content of species ranged from 2C = 3.45 pg in Brassavola nodosa to 2C = 7.96 pg in C. guttata. The leaf tissues of the analyzed representatives presented endoreduplication cycles in most species. Our data suggest that although it occurs an apparent macrostructural stable karyotype (2n = 40) in the species of the subtribe Laeliinae as well as the genus Cattleya studied, they present a pattern of diversification of heterochromatin consistent with the phylogenetic clusters and identify possible sinapomorphies that allow better understanding of taxonomically complex species.